"Built‐in" PD‐1 blocker to rescue NK‐92 activity from PD‐L1–mediated tumor escape mechanisms. Issue 9 (23rd August 2021) - Mensali, Nadia; Dillard, Pierre; Fayzullin, Artem; Köksal, Hakan; Gaudernack, Gustav; Kvalheim, Gunnar; Inderberg, Else Marit; Wälchli, Sébastien
Abstract: Success of adoptive cell therapy mainly depends on the ability of immune cells to persist and function optimally in the immunosuppressive tumor microenvironment. Although present at the cancer site, immune cells become exhausted and/or inhibited, due to the presence of inhibitory receptors such as PD‐L1 on malignant cells. Novel genetic strategies to manipulate the PD1/PD‐L1 axis comprise (i) PD‐1 reversion where the receptor intracellular domain is replaced with an activating unit, (ii) the use of anti‐PD‐L1 CAR or (iii) the disruption of the PD‐1 gene. We here present an alternative strategy to equip therapeutic cells with a truncated PD‐1 (tPD‐1) to abrogate PD‐1/PD‐L1 inhibition. We show that engagement of tPD‐1 with PD‐L1‐positive tumor unleashes NK‐92 activity in vitro. Furthermore, this binding was sufficiently strong to induce killing of targets otherwise not recognized by NK‐92, thus increasing the range of targets. In vivo treatment with NK‐92 tPD‐1 cells led to reduced tumor growth and improved survival. Importantly, tPD‐1 did not interfere with tumor recognition in PD‐L1 negative conditions. Thus, tPD‐1 represents a straightforward method for improving antitumor immunity and revealing new targets through PD‐L1 positivity.